MANAJEMEN PENGELOLAAN LAHAN KRITIS PADA DAS BRANTAS HULU BERBASIS MASYARAKAT (Pilot Project Desa Bulukerto, Kota Batu) - Sri Harini, Suyono, Elok Mutiara (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
Management of critical farm base on society represents a new approach to all researcher of environment this time. In management of farm base on this society, society invited directly start from planning, formulation of policy, its benefit collection and execution. With this direct participation enable society can calculate directly impact economical and environment (natural resources conservation), because this two aspect represent two inseparable aspect in doing study management of SDA, because having very important role in supporting efficacy of program of Participatory Action Research (PAR). Pursuant to result of discussion and dig of information of society hence a success main problem identified with society member pursuant to antecedent study (research preliminary) which have been conducted by researcher related to program management of critical farm base on society taken as focus in enable ness is critical condition survey of forest farm, socialization of UU No. 32 year 2009 about management and protection of environment, socialization and training of system of terasiring pattern and plant real correct at farm with high inclination ( 450) having economic value and with vision of environment. Marginally cycle of PAR conducted at this enable ness program is to use technical method, mapping, transect, diagram of Venn, change schema and of livelihood analysis. By using this approach is expected by society have awareness in managing and exploiting environment real correctly. Besides society can direct control to all impact and policy of the policy because related to source of their residence environment and living. Keywords : Erosion, Critical Farm, Research Preliminary, Participatory Action Research, Mapping, Transect, Diagram of Venn, Change Schema, Analysis livelihood